1971
DOI: 10.1017/s0003356100010734
|View full text |Cite
|
Sign up to set email alerts
|

The effect of food restriction on subsequent voluntary intake of pigs

Abstract: SUMMARYA total of 64 nine-week-old pigs were used in two experiments to study the influence on feed intake, growth and carcass quality of dietary restriction at various ages or live weights. Two diets of different energy content were given throughout each experiment, which was divided into four periods on either an age or weight basis. Feed was restricted or offered ad libitum during each of the first three periods, all pigs being fed ad libitum during the last period.Compensatory intake following a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 5 publications
5
11
0
Order By: Relevance
“…On being given free access to the food in the second period, the R pigs could be expected to increase their rate of food intake from 300 g/day in order to attain their potential growth rate and to attempt to eliminate their lipid deficit (Cole et ah, 1968;Owen et , 1971;Ratcliffe and Fowler, 1980). To be able to process the greatly increased intake they would need to grow their food-processing organs rapidly which, in turn, would further increase the demand for food.…”
Section: Discussionmentioning
confidence: 99%
“…On being given free access to the food in the second period, the R pigs could be expected to increase their rate of food intake from 300 g/day in order to attain their potential growth rate and to attempt to eliminate their lipid deficit (Cole et ah, 1968;Owen et , 1971;Ratcliffe and Fowler, 1980). To be able to process the greatly increased intake they would need to grow their food-processing organs rapidly which, in turn, would further increase the demand for food.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported by Sobinson (1964) and Owen, Ridgman and Wyllie (1971) when larger pigs were restricted-fed. Topel (1971) and Young and Sharma (1973) attempted to evaluate the effect of early energy restriction per se on subsequent performance and concluded that energy intake from birth to 23 kg live weight has no effect on body composition of market pigs.…”
Section: Nutrition and Compensatory Growth In Pigssupporting
confidence: 91%
“…During the following period of realimentation this difference decreased to 5% but, compared with pigs continuously fed the HF diet, it was 3% lower. Comparison of the voluntary feed intake of compensating pigs in our study with that of pigs previously restricted with protein or feed/energy intake, it is clear that they responded rather similarly to the latter (Owen et al, 1971;Bikker, 1994;Skiba et al, 2001), as animals on which compensatory growth was induced by previous protein restriction do not consume more feed (de Greef, 1992;Skiba et al, 2001).…”
Section: Discussionmentioning
confidence: 69%